Overview of cardiovascular manifestations of COVID-19 and echocardiographic features - Meel, Ruchika; Gonçalves, Ricardo (SA Heart Journal, 2020)
COVID-19 or SARS-CoV-2, a novel coronavirus, has rapidly spread across the globe, resulting in millions of infections and thousands of deaths. In this short review we describe the pathophysiology, clinical and echocardiographic manifestations of the virus, with specific reference to the cardiovascular system. We conclude with a case summary reflective of the most common cardiovascular presentation in severely ill patients.